Removing Statutory and Administrative Barriers to Library Development in Ghana - Arkaifie, Richard (Ghana Library Journal, 1997)
Some legal provisions which were introduced some decades ago to enhance the growth and development of libraries have become anachronistic with the passage of time and our inability to revise and bring them in line with current trends constitutes a barrier to Library development. In much the same vein, our lack of resolve to introduce legislation which might contribute to information provision and some administrative decisions or indecision can be considered to be barriers to development.